THE EFFECT OF USING RECONSTRUCTION CLOZE TASKTOWARD STUDENTS’ GRAMMAR MASTERY AT IAIN BUKITTINGGI - Veni Roza; Rika Fitriani; Jondra Nikmat (English Language Teaching and Research, 2017)
The research was due to some problems related to grammar teaching carried out by lecturers. The method used in teaching grammar was still deductive method, the students were lack of grammar practice in context, the average of students’ grammar test result was still unsatisfying and they were also less active in learning. The aim of the research is to find out the effect of using Reconstruction Cloze Task toward students’ grammar mastery in past perfect tense. The type of this research is a quasi-experimental research. To choose samples, the researcher usedPurposive Sampling Technique with the consideration of the same level ability that is IIA and IIB. To analyze the data, the researcher used the independent t-test by using SPSSS software. The finding reveals that there is significant effect of using Reconstruction Cloze Task toward students’ grammar mastery in past perfect tense. Based on students’ gain scores at pretest and post-test scores in the both experimental and control classes, the researcher found the score of ½ Sig. for two-tailed test for homogenous variances is .00 which is smaller than alpha (0.05). Since the score of ½ Sig. of independent sample test does not exceed alpha 0.05, alternative hypothesis (Ha) is being accepted. In conclusion, the use of Reconstruction Cloze Task in teaching grammar effectively improves students’ grammar mastery. Key words: Reconstruction Cloze Task, Grammar Mastery, Past Perfect Tense